2006
DOI: 10.4269/ajtmh.2006.74.376
|View full text |Cite
|
Sign up to set email alerts
|

Parasitemia, Anemia, and Malarial Anemia in Infants and Young Children in a Rural Holoendemic Plasmodium Falciparum Transmission Area

Abstract: Malarial anemia (MA) is a multifactorial disease for which the complex etiological basis is only partially defined. The association of clinical, nutritional, demographic, and socioeconomic factors with parasitemia, anemia, and MA was determined for children presenting at a hospital in a holoendemic area of Plasmodium falciparum transmission in western Kenya. Parasitemia was not associated with malaria disease severity. In univariate logistic regression, fever was significantly associated with parasitemia, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
126
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(139 citation statements)
references
References 35 publications
12
126
1
Order By: Relevance
“…These results suggest that the pattern of IL-23, IL-12, and IL-10 production observed in children with malarial anemia in the current study were significantly influenced by the strong relationship between parasite density and production of these cytokines. It is also important to point out that in this population of children, we have consistently observed that parasitemia is not strongly associated with malarial anemia severity [29,35,38]. This could explain, at least in part, our observation that the absolute levels of these cytokines were comparable between the MlMA and SMA groups.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…These results suggest that the pattern of IL-23, IL-12, and IL-10 production observed in children with malarial anemia in the current study were significantly influenced by the strong relationship between parasite density and production of these cytokines. It is also important to point out that in this population of children, we have consistently observed that parasitemia is not strongly associated with malarial anemia severity [29,35,38]. This could explain, at least in part, our observation that the absolute levels of these cytokines were comparable between the MlMA and SMA groups.…”
Section: Discussionmentioning
confidence: 71%
“…SMA is the primary clinical manifestation of severe malaria in children under the age of 5 years in this region, with the peak incidence of malarial anemia occurring in children 7-24 months of age [5,34]. A detailed description of the study area and the hematological manifestations of pediatric malarial anemia (MA) in the study population can be found in our recent publication [35].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…20 records met our inclusion criteria (table), [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] and of these 15 contained the necessary data for inclusion in the quantitative analysis (meta-analysis). Five records were excluded from the quantitative analysis either because Bayesian credible intervals were reported (n=2) or because ORs could not be calculated from the available data (n=3)[A: sentence correct as edited?].…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] In addition to destruction of infected and uninfected red blood cells, insufficient erythropoiesis, due to either ineffective erythropoiesis and/or dyserythropoiesis, plays a key role in malarial anemia. 5,6 Deficient erythropoietin (EPO) production does not appear to provide an explanation for malarial anemia since most studies indicate that EPO production is adequately increased in response to the level of anemia.…”
Section: Introductionmentioning
confidence: 99%